The transmission curve of a fabry perot system based on plane and spherical mirror separation - Esa, Fahmirudin (2009)
The purpose of this study is to investigate the transmission curve of multiple reflections, which is known as Fabry Perot interferometer based on spherical and plane mirror separation. This multiple reflections of light should occur between two high reflectance coefficients of parallel mirrors that are named as cavity before they get to be transmitted. The transmitted rays along the edge of secondary mirror were observed. The highest interference peak occurs when they experienced same phase. These transmitted rays then were scanned by periodic linear change in the Piezo voltage that had been set at 128 V and its frequency was tuned up to 100 Hz. Proper alignment on setup arrangement and some modification of the system had been done and the captured data effectively clarified by theoretical approach. The cavity was fixed set as the radius of curvature for confocal measurement; there were 75 mm and 100 mm whereas for plane parallel distance was set from 250 mm of separation until 400 mm improved by 50 mm every increment. Free spectral range parameters for confocal separations were 166.551 MHz per division for 75 mm and 124.914 MHz per division for 100 mm separation. Based on the waist of the Gaussian beam, the slimmer of full wave half maximum was owned by the separation of 75 mm. Based on high reflectance coefficient, the calculated value of finesse was 76.953. More difficult adjustment had been encountered while testing the plane parallel mirror. The more sensitive, probably in micro meter changed, opto-mechanical system on the piezo electric scanning should be required.